PROGRAM RUMAH CERDAS DIGITAL SEBAGAI UPAYA PENINGKATAN LITERASI DIGITAL DI DESA MALLONGI-MALLONGI - Dassa, Awi; Assagaf, Said Fachry; Herman, Herman; Putri, Ardita Amelia; Putra, Arianto Dwi (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2024)
Digital literacy can be defined as the ability to use and understand information from a very wide range of sources that can be displayed on computer devices. The measurement of the digital literacy index is seen from four dimensions, namely, digital skills, digital ethics, digital security, and digital culture. When measured against these four dimensions, the level of digital literacy, Mallongi-Longi Village is considered as low in its application. Therefore, the Student Activity Unit  (PPK Ormawa) of the Mathematics Department at FMIPA UNM seeks to address the issues in Mallongi-Longi Village by implementing a work program called the Digital Smart Home Program. It is hoped that this Smart Home Program can broaden the knowledge, attitudes, and skills of the Mallongi-Lonngi Village community regarding digital literacy. This program is conducted through classes and seminars. It consists of two main activities, namely digital classes and digital workshops, targeting the Mallongi-Longi Village community. This program runs for 58 days. Based on the program evaluation results, it was found that the target participants have responded well, the target community wants the sustainability of this program and this program has achieved all the objectives of the program implementation.